Dietary niche and gut microbial responses to novel environment in bank voles artificially selected for herbivorous capability - Vuori, Tommi (2023)
Evolution of dietary niche and gut microbiota may be driven by natural selection acting on behavioral or physiological traits. However, relative importance of genetic and environmental components remain unclear. In this thesis I conducted a lab-to-field translocation experiment using bank vole selection lines with artificially enhanced capability to maintain body mass with low-quality fiber-rich diet (H-line) and unselected control lines (C-line). Objectives of this study were to investigate 1) if overall genotypic differences that result from artificial selection for whole-organism performance are coupled with dietary niche divergence and 2) whether responses of gut microbiota of the selection lines differ when translocated from field to laboratory. Realized diets of the bank voles in the field conditions were determined using stable isotopes analysis for carbon and nitrogen in bank vole liver tissues. Gut microbial responses were examined using repeated fecal sampling and 16S rRNA-V4 amplicon sequencing. Indicated by stable isotopes of nitrogen, H-line appeared to consume food from the lower trophic level than C-line. Moreover, interestingly, carbon sources differed between the selection lines in juveniles but not in adults. However, environmental variation seemed to explain remarkable proportion of dietary variation. While translocation from the laboratory to field conditions induced different gut microbial responses between lines, the effects of environmental factors in relation to host traits were notable. Taken together, the results presented in this thesis are in line with previous research and indicate that the selection for physiological or behavioral performance can result to modifications in dietary niche and gut microbiota. These results call for further research on the assessment of long-term trends of these findings.